Salivary IgA as a risk factor for upper respiratory infections in elite professional athletes - Neville, V.; Gleeson, M.; Folland, J. P. (Medicine & Science in Sports & Exercise, 2008)
The relationship between physiological and psychological stress and immune function is widely recognized; however, there is little evidence to confirm a direct link between depressed immune function and incidence of illness in athletes.